Expanding Nuclear Physics Horizons with the Gamma Factory. Issue 3 (31st January 2022) - Budker, Dmitry; Berengut, Julian C.; Flambaum, Victor V.; Gorchtein, Mikhail; Jin, Junlan; Karbstein, Felix; Krasny, Mieczyslaw Witold; Litvinov, Yuri A.; Pálffy, Adriana; Pascalutsa, Vladimir; Petrenko, Alexey; Surzhykov, Andrey; et al.
Abstract: The Gamma Factory (GF) is an ambitious proposal, currently explored within the CERN Physics Beyond Colliders program, for a source of photons with energies up to ≈400 MeV and photon fluxes (up to ≈10 17 photons s −1 ) exceeding those of the currently available gamma sources by orders of magnitude. The high‐energy (secondary) photons are produced via resonant scattering of the primary laser photons by highly relativistic partially‐stripped ions circulating in the accelerator. The secondary photons are emitted in a narrow cone and the energy of the beam can be monochromatized, down to 10 −3 –10 −6 level, via collimation, at the expense of the photon flux. This paper surveys the new opportunities that may be afforded by the GF in nuclear physics and related fields. Abstract : The Gamma Factory is an ambitious proposal for a source of photons with energies up to hundreds of MeV and photon fluxes exceeding those of the currently available gamma sources by orders of magnitude. The paper surveys the new opportunities in nuclear physics and related fields that may be afforded by the this facility.